Shapeshifting RNAs guide innate immunity - Dinman, Jonathan D. (J Biol Chem, 2018)
The innate immune system can distinguish between RNAs of viral and cellular origin, but the basis for this discrimination is not known. A new paper by Calderon and Conn demonstrates that conformational plasticity determines the ability of one RNA sequence to bind to and activate the pattern recognition receptor OAS1/RNase L. In identifying a novel mode through which the immune response is naturally controlled, this finding opens new avenues toward developing approaches for the management of a wide range of viral infections.